2016
DOI: 10.1007/s12160-016-9869-6
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Smoking Cessation: Evidence from a Smoking Cessation Clinic with 1-Year Follow-Up

Abstract: Background Smoking is more prevalent among people with depression. Depression may make cessation more difficult and cessation may affect depression symptoms. Purpose The aims of this study were to assess the associations between (1) baseline depression and 1-year smoking abstinence and (2) abstinence and change in depression. Methods Observational study using data collected routinely in a smoking cessation clinic in the Czech Republic from 2008 to 2014. Aim 1: N = 3775 patients; 14.3% reported mild and 15.4% m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
3
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 37 publications
5
37
3
4
Order By: Relevance
“…35,36 A study reported that smoking cessation led to depression, 37 suggesting that it might be better to let depressed patients smoke, thereby discouraging the smoking cessation recommendation to these patients. However, given mounting evidence on how to treat smoking patients with mental disorders, 38 and the latest empirical evidence suggesting that smoking cessation actually decreases depression, 39,40 it is worth focusing more on smoking cessation among patients with conditions such as depression.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 A study reported that smoking cessation led to depression, 37 suggesting that it might be better to let depressed patients smoke, thereby discouraging the smoking cessation recommendation to these patients. However, given mounting evidence on how to treat smoking patients with mental disorders, 38 and the latest empirical evidence suggesting that smoking cessation actually decreases depression, 39,40 it is worth focusing more on smoking cessation among patients with conditions such as depression.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 A study reported that smoking cessation led to depression, 37 suggesting that it might be better to let depressed patients smoke, thereby discouraging the smoking cessation recommendation to these patients. However, given mounting evidence on how to treat smoking patients with mental disorders, 38 and the latest empirical evidence suggesting that smoking cessation actually decreases depression, 39,40 it is worth focusing more on smoking cessation among patients with conditions such as depression.…”
Section: Discussionmentioning
confidence: 99%
“…distress in patients with [36] and without [37] clinical levels of depression and anxiety. Similarly, reductions in smoking can also lead to reductions in psychological distress [38], but as depression severity is related to the likelihood of cessation success [38], there may be a need to treat the psychological distress in parallel with smoking cessation. The addition of psychosocial support to smoking cessation interventions has been shown to increase long-term cessation rates in smokers with depression in contrast to smoking cessation alone [39].…”
Section: Level Of Copd Riskmentioning
confidence: 99%